Raising the Standard of Abortion Informed Consent: Lessons to be Learned from the Ethical and Legal Requirements for Consent to Medical Experimentation - Seo, Jennifer Y. (Columbia Journal of Gender and Law, 2011)
In the aftermath of Planned Parenthood of Southeastern Pennsylvania v. Casey,’ state legislatures have restricted access to abortions by regulating the informed consent process. Taking as an invitation the Court’s holding that a state is permitted “to further its legitimate goal of protecting the life of the unborn by enacting legislation aimed at ensuring a decision that is mature and informed, even when in so doing the State expresses a preference for childbirth over abortion,”2 states began to legally mandate specific required disclosures, language, or procedures for obtaining informed consent to abortions. While all states require informed consent before medical procedures either by statute or by case law, the details of the process have .traditionally been self-regulated by the medical profession through medical ethics.3 Currently, thirty-four states have abortion-specific informed consent statutes.4 However, these statutes mandate disclosures of information that not only go beyond what is required for other medical procedures, but also include information that is inaccurate, incomplete, or irrelevant to the particular abortion procedure to be performed. Thus, states, under the shield of the Casey decision, have used abortion informed consent statutes to express their preference for childbirth over abortion in a way that serves to unduly influence a woman’s choice, in violation of the ethical boundaries of medical informed consent.